(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
يتناول هذا البحث دور التنغيم في تحديد معنى الجملة العربية. يبدأ البحث بتناول وجود التنغيم في التراث العربي عند الدَّارسين المعاصرين, ومع أنَّه اتخذ عندهم اتجاهاتٍ مختلفة، ولكنَّه لم يحظَ لدى أجدادنا ببحث مستفيض, أو تطبيق مستند إلى قواعدَ محدَّدة, وأنَّ هذا يعني هذا أنَّ تراثهم الواسع خلا من إشارات إلى هذه الظاهرة الصوتية المؤثّرة في المعنى, ولكنّهم مجمعون على ارتباطه بالجمال الفنِّي ارتباطاً وثيقاً، وأنه القاسم المشترك بين الفنون جميعاً, ومن هنا ارتبط التنغيم كقرينة لفظية في التعبير عن المعاني النّفسيّة والنّحوية ارتباطاً جعله من أهمّ الأدوات ذات التأثير في نفس القارئ, أو المتلقِّي ووجدانه. يحاول البحث الوقوف على رصد أثر التنغيم في تفسير قضايا نحويّة, وتركيبية, وصرفيّة وصوتيّة ودلاليّة في اللغة العربية من خلال إدراج مستوياته اللحنيّة ووظائفه المختلفة في التعبير عن بعض المعاني النّفسيّة والنّحوية, وكما يتوخّى الكشف عن الاختلافات في النطق التي تتميز بها اللهجات المختلفة التي لا تظهر في الكتابة, لأنَّها لا تملك ما يملكه المتكلِّمون من نغمات في الصّوت لتوضيح الكلام الملفوظ. وينتهي البحث بالحديث عن سرِّ الجمال الفني للتنغيم ودوره في التفريق بين معاني الجمل والمقولات النّحوية وطرق القواعد النّحوية, والكشف عن الأماكن الكامنة وراء الظاهرة من التشكيلات والمعاني. This paper deals with the role of intonation in defining the meaning of the Arabic sentence. The paper shows that intonation in Arabic tradition was dealt with by contemporary researchers. However, it was not adequately analyzed by our ancestors, though it manifested itself in many ways. There were many references to this phonetic phenomenon that affects meaning; and the ancestors unanimously agreed that it was closely connected with aesthetic beauty and all arts. This is why intonation, as a verbal expression of psychological and grammatical meanings, is one of the important tools effective in both the reader and recipient. This paper traces the role of intonation in interpreting grammatical, syntactical, derivational, phonetic, and semantic issues in Arabic through elucidating the various tuning levels and functions of intonation in expressing some psychological and grammatical meanings. It also seeks to reveal the varieties of pronunciation with which accents are characterized, and that do not appear in writing. This is because writing does not have what speakers show of tones of voice to illustrate spoken words. The paper ends by explaining the secret of the aesthetic beauty of intonation and its role in distinguishing between meanings of sentences and grammatical rules and statements as well as revealing the potential meanings and structures of this phenomenon.